FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PEMBELIAN DENGAN PERILAKU NIAT SEBAGAI VARIABEL INTERVENING PADA SITUS KASKUS - WIBISONO, YUNGKY HARI (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The number of internet users and also the users of the site kaskus which increased caused consumers purchase online on website kaskus has increased. This research was conducted to determine the influence of purchasing power, perceived ease of use, and social influence to purchase behavior through the behavioral intention on kaskus. The population in this research is amazed that never make a purchase on the site a year ago by the longest with a total sample of research as much as 150 respondents. Sampling technique that is used is a non probability sampling by means of purposive sampling technique in which the determination of samples with specific considerations, namely the respondents never make a purchase on the site by at least 1 times, within 1 years and the age of the respondents a minimum of 15 years. Technique of data analysis using Structural Equation Modeling (SEM). The results showed that the purchasing power has an impact on behavioral intention on the website of kaskus, perceived ease of use has an impact on the behavior of intention on kaskus, social influence has an impact on behavioral intention on the website of kaskus, and behavioral intention has an impact on purchase behavior on kaskus.